2005
DOI: 10.1165/rcmb.2004-0405oc
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GPRA, a Novel G Protein–Coupled Receptor Related to Asthma

Abstract: We recently identified a novel positional asthma susceptibility gene, GPRA, which belongs to the G protein-coupled receptor family. In the present studies, we show that isoform specific activation of GPRA-A with its agonist, Neuropeptide S (NPS) resulted in significant inhibition of cell growth. GPRA has several variants due to extensive alternative splicing. We observed that only the full-length variants, GPRA-A and GPRA-B, with 7 transmembrane topology are transported into the plasma membrane, while the trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 19 publications
4
91
2
1
Order By: Relevance
“…Activation of NPSR by NPS results in increased intracellular cAMP levels and Ca 2ϩ mobilization, leading to the conclusion that it is coupled to G s and G q proteins (7,9). Reinforcing the genetic evidence that NPSR is involved in asthma, it has been reported that expression of the NPSR-B isoform, but not the NPSR-A isoform, is increased in bronchiolar smooth muscle and epithelial cells of asthmatics compared with healthy controls (4,12). It has also been shown that lung NPSR is up-regulated in a murine model of allergic asthma (4).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Activation of NPSR by NPS results in increased intracellular cAMP levels and Ca 2ϩ mobilization, leading to the conclusion that it is coupled to G s and G q proteins (7,9). Reinforcing the genetic evidence that NPSR is involved in asthma, it has been reported that expression of the NPSR-B isoform, but not the NPSR-A isoform, is increased in bronchiolar smooth muscle and epithelial cells of asthmatics compared with healthy controls (4,12). It has also been shown that lung NPSR is up-regulated in a murine model of allergic asthma (4).…”
mentioning
confidence: 98%
“…One of these, GPR154, encoding neuropeptide S receptor (NPSR) 4 (4,7), also known as G protein receptor for asthma susceptibility (GPRA) (4), GPR154 (8), and vasopressin receptor-related receptor 1 (VRR1) (9), has been confirmed as an asthma-linked gene in five distinct Caucasian populations (4,10,11). The gene for NPSR encodes at least two splice variants that differ only in their C termini (4,12) and are referred to herein as NPSR-A and NPSR-B, corresponding to GPRA-A and GPRA-B (4), respectively. A number of single nucleotide polymorphisms in the NPSR sequence are associated with asthma, elevated serum IgE levels, and bronchial hyperresponsiveness (4,10,11).…”
mentioning
confidence: 99%
“…Interestingly, another isoform, the short one that is expressed in intracellular compartments does not affect the cell surface expression of the full-length receptors when co-expressed [67].…”
Section: Alternative Splicing Of Gpcr In Other Pathophysiological Conmentioning
confidence: 97%
“…A genome-wide scan suggested that one of the contributory factors to asthma and other IgE-mediated diseases could be GPRA (also known as GPR154 and the neuropeptide S receptor) [134]. Several splice variants of the receptor have been described [67]. Two splice variants that encode GPRA isoforms with distinct C-termini (termed A and B isoforms) are full-length isoforms that traffic to the plasma membrane.…”
Section: Alternative Splicing Of Gpcr In Other Pathophysiological Conmentioning
confidence: 99%
See 1 more Smart Citation